2D−3D crossover of the in-plane paraconductivity in optimal doped ReBa₂Cu₃O₇₋δ (Re = Y, Ho) single crystals - Vovk, R.V.; Obolenskii, M.A.; Bondarenko, A.V.; Goulatis, I.L.; Chroneos, A.I. (Физика и техника высоких давлений, 2007)
The effect of the fluctuation paraconductivity in optimal oxygen-doped ReBa₂Cu₃O₇₋δ (Re = Y, Ho) single crystals has been investigated. The results indicate that the theoretical model of Aslamazov–Larkin (AL) describes the temperature dependence of fluctuation paraconductivity (FP) near the critical temperature (Tc). At temperatures above the temperature of the 2D−3D crossover this dependence is appropriately described by the Lawrence–Doniach (LD) theory. The extended linear dependence of ρab(Т), in the crystal with the minimum critical temperature indicates that we have a high defect concentration in this sample. This in turn causes negative processes into forming fluctuation pairs.